2005
DOI: 10.2298/jsc0501009m
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the thermodynamic properties of the Ga-Sb-Tl liquid alloys

Abstract: The results of the calculation of the thermodynamic properties for liquid Ga-Sb-Tl alloys at the temperature 1073 K are presented in this paper. Initially, the most appropriate thermodynamic model for the investigated system was selected. Based on a comparison of the values calculated by different geometric models (Kohler, Muggianu, Toop, Hillert, Chou) with the existing experimental based data, asymmetric models of calculation were determined to give the best results. The asymmetric nature of the investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The methods to estimate the thermodynamic properties of ternary system by means of extrapolation from constitutive binary systems include symmetric and asymmetric ones [3][4][5][6][7][8][9][10]. The prediction methods of formation enthalpy for multicomponent system based on Miedema's theory were also proposed [11][12][13] since the formation enthalpies of most of binary systems can be calculated with Miedema's theory [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The methods to estimate the thermodynamic properties of ternary system by means of extrapolation from constitutive binary systems include symmetric and asymmetric ones [3][4][5][6][7][8][9][10]. The prediction methods of formation enthalpy for multicomponent system based on Miedema's theory were also proposed [11][12][13] since the formation enthalpies of most of binary systems can be calculated with Miedema's theory [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The methods to extrapolate thermodynamic properties of ternary systems from constitutive binary systems include symmetric and asymmetric methods [1][2][3][4][5][6][7][8]. The prediction methods of enthalpy of formation of multi-component systems based on Miedema's theory were also proposed [9][10][11][12] since the enthalpies of formation of most of binary systems can be calculated with Miedema's theory [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Integral excess Gibbs energies of mixing were derived according to Darken's method from the two binary data of Ga-Sb and Ga-Tl systems combined with the ternary data along pseudobinary system of (Sb y Tl 1-y )-Ga (** in the Table ) and also from the combination of the ternary data and basal binary data of Sb-Tl system (* in the Table ). Dragan et al [4] reported the thermodynamic properties in this system at 1073K obtained by use of several thermodynamic models [5] based on the constituent three binary data; Ga-Sb [1], Ga-Tl [2] and Sb-Tl [6]. One of the results is shown in Fig.…”
mentioning
confidence: 99%